Stress Management During Covid-19 Pandemic by Consuming Herbal and Alternative Medicine – A Cross Sectional Study (Medical Forum Monthly, 2024)
Objective: Main objective of current study was to investigate the frequency of the use of herbs and alternative-medicine during Covid-19 and their effectiveness in reducing stress.Study Design: Cross-sectional surveyPlace and Duration of Study: This study was conducted at the Faculty of Pharmacy and Pharmaceutical Sciences and Faculty of Arts and Social Sciences, University of Karachi from August 2022 to June 2023.Methods: The collection of the data was done by survey questionnaire. Ethical approval of study has been taken from Ethical Review Committee, Hamdard University. Chi-square and correlation tests were applied for determination of significance between variables.Results: The data for current study was collected from 332 participants. Majority of respondents were 18-30 years old, followed by 31-40 years. Respondents mentioned that black seeds, citrus fruits, ginger, herbal teas and honey consumption reduced the stress during lockdown of Covid-19 outbreak (χ2=1192.35; p=0.0051). Effects of rumors were high on individuals during pandemic for causing anxiety (χ²=975.92; p=0.0049). Similarly majority of individuals mentioned that herbal remedies were significantly (χ²=960.42; p=0.031) effective in reducing stress during Covis-19 lockdown. Low income individuals preferred to use herbal medicine during pandemic (χ2=1188.0; p=0.0001). Conclusion: Herbal and alternative medicines can significantly contribute in boosting the immune strength of individuals with cost-effectiveness. Effectiveness of herbal products for relieving stress during Covid-19 was high.